Policy Advocacy Network in Support of the Expansion of the New South Garut Autonomous Region - Diki Suherman; Yogi Suprayogi Sugandi; Mohammad Benny Alexandri (Indonesian Association for Public Administration, 2021)
The purpose of this study was to determine the policy advocacy network in support of the expansion of the new South Garut autonomous region. The method used in this study used a qualitative descriptive approach. The technique of collecting data through interviews and documentation, informants were selected based on purposive sampling and snowball. The data analysis technique used is an interactive analysis model including data reduction, data presentation (display) and drawing conclusions. The results of this study are that the Policy Advocacy Network in supporting the expansion of the New South Garut Autonomous Region, has so far made efforts to support the expansion with their respective roles. Both from South Garut academics, South Garut community leaders, especially the expansion presidium who are representatives of the South Garut community and the Garut district government itself as policy makers at the district / city level. The three actors of course network with each other to support the division of South Garut into a new district in West Java, through procedures that are regulated in accordance with the applicable laws and regulations in establishing a new autonomous region.